Employment of Audit Risk Models - Jankūnaitė, Rita; Kanapickienė, Rasa; Gipienė, Gailutė (Ekonomika, 2005)
Different audit risk evaluation models presented in the literature and looks into their advantages and disadvantages are analysed. However, scientific works do not offer a universal audit risk evaluation model to make the auditor’s life easier when the audit risk has to be evaluated. Following the research of audit risk evaluation performed by Lithuanian auditors and in view of the related models provided in the literature, some improvements to the audit risk model are proposed, which enable evaluating the audit risk components, i.e. the audit risk structure, and reveals the consistency of audit risk evaluation in the auditing process, i.e. discloses the dynamic picture of the audit.